Burning Japan : Air Force bombing strategy change in the Pacific - Schwabe, Daniel T., 1980- (Potomac Books, an imprint of the University of Nebraska Press, 2014)
Burning Japan is an investigation of how and why the air force shifted its tactics against Japan from a precision bombing strategy to area attacks. The guiding doctrine of the 1930s and 1940s called for focused attacks on specific targets deep behind enemy lines. Eager to prove itself, the nascent Army Air Force at first lauded the indispensability of strategic bombardment in areas otherwise unreachable by the army or navy. But when strategic bombing failed to yield the desired results in Europe and in initial efforts against Japan, the United States switched tactics, a shift that culminated i.